Environmental and economic attitudes from visitors of Mediterranean Geoparks. - Dos-Santos, M.; Isabel Andrés Marques; Mafalda Mendes-Ribeiro (Goldsmith, 2014)
Mediterranean geoparks play an important role on the conservation and sustantability socio-environmental . Although the number of visitors are decreasing due to economic and financial crisis that affect the mediterranean countries, there are still greatest oportunities in new marketing strategies in order to preserve the environmental caracteristics and strengthen new tourist activities, services and products. The main goal of this paper is to identify the environmental attitudes of the geoparks´ visitors and to relate them with the environmental strategies of conservation, the needs of new touristic products and marketing strategies. To find that, we apply 2232 questionaires to visitors of geoparks in Portugal, Italy and Greece. The metodology selected was according Dos-Santos (2013), but adjusted and include multivariate analysis, namely, Components of Principal Analysis and cluster analysis to form homogeneous groups of tourists and a multinomial probit model in order to determine the main factors that visitors from this mediterranean countries attentant. The results present four groups of visitors according to environmental, economic and social caracteristics. There are no significant differences among the visitors from the three countries. The main conclusions suggest the need of a common strategy of preservation of the hight environmental value in the geoparks and the introduction of new services along with a marketing strategy including educational and training support. The main results of the survey are in line with other authors, namely, the emphasis that geoparks in mediterranean countries must be based on geological heritage and its preservation in addition to ecological, cultural, historical and archaeological aspects